Temporal Behavior of Capsule Enlargement by Cryptococcus neoformans - Cordero, Radames J. B. (American Society for Microbiology, 2013)
Microbial capsules are important virulence traits that mediate cell-host interactions and provide protection against host immune defense mechanisms. Cryptococcus neoformans is a yeast-like fungus that is capable of synthesizing a complex polysaccharide (PS) capsule that is required for causing disease. Microscopic visualization of capsule enlargement is difficult, because the capsule is a highly hydrated structure with an index of refraction that is very close to that of aqueous medium. In this study, we took advantage of the capsular reaction (“quellung” effect) produced by IgM monoclonal antibody (MAb) 13F1 to increase the refraction index difference between capsule and medium such that we visualized the capsule using differential interference contrast (DIC) microscopy. Time-lapse size measurements allowed us to quantify the growth rate of the capsule relative to that of the cell body. The increase in capsule volume per unit of time was consistent with a logistic variable slope model in which the capsule's final size was proportional to the rate of its growth. The rate of capsule growth (0.3 to 2.5 µm(3)/min) was at least 4-fold faster than the rate of cell body growth (0.1 to 0.3 µm(3)/min), and there was large cell-to-cell variation in the temporal kinetics of capsule and cellular growth. Previous to the first cellular replication event, both the capsule and cell body enlarged simultaneously, and their differences showed monotonic growth, which was affected only by its rate of volume increase per unit of time. Using these results, we provide an updated model for cryptococcal capsule biogenesis.